3D numerical study on fracture process of concrete with different ITZ properties using X-ray computerized tomography. (15th August 2018) - Yu, Qinglei; Liu, Hongyuan; Yang, Tianhong; Liu, Honglei
Abstract: A three-dimensional (3D) realistic numerical modelling method is proposed to simulate the fracture process of concrete based on its meso-structure. In the 3D realistic numerical modelling method, CT technology is first applied to capture the microstructure of the concrete as a series of cross-sectional CT images. An improved digital image processing (DIP) technique is then developed to identify and characterize the aggregates and the interfacial transition zones (ITZ) in the CT images. After that, a 3D realistic three-phase structure model of the concrete is reconstructed on the basis of the processed CT images using the vectorized transformation and volume rendering method, which is integrated into a well-established 3D Realistic Failure Process Analysis (RFPA 3D ) code. In this way, the 3D realistic numerical modelling method is developed. It is validated by building a 3D realistic numerical model of the concrete and comparing the results between numerically and experimentally obtained. Finally, using the 3D realistic numerical modelling method, the effects of the ITZ strength on the fracture process of the concrete under uniaxial compression and tension are studied and further clarified. The proposed 3D realistic numerical modelling method provides a new tool to study the fracture mechanism of concrete at the mesoscopic/microscopic levels under complex loading conditions.